The shadow economy : an international survey - Schneider, Friedrich; Enste, Dominik (Cambridge : Cambridge University Press, 2013)
Illicit work, social security fraud, economic crime and other shadow economy activities are fast becoming an international problem. This second edition uses new data to reassess currency demand and the model approach to estimate the size of the shadow economy in 151 developing, transition, and OECD countries. This updated edition argues that during the 2000s the average size of the shadow economy varied from 19 per cent of GDP for OECD countries, to 30 per cent for transition countries, to 45 per cent for developing countries. It examines the causes and consequences of this development using an integrated approach to explain deviant behaviour that combines findings from economic, sociological, and psychological research. The authors suggest that increasing taxation and social security contributions, rising state regulatory activities, and the decline of the tax morale are all driving forces behind this growth, and they propose a reform of state public institutions in order to improve the dynamics of the official economy.
The shadow economy : a challenge for economic and social policy -- Defining the 'shadow economy' -- Methods to estimate the size of the shadow economy -- Size of shadow economies around the world -- The size of the shadow-economy labour force -- An integrated approach to explain deviant behaviour -- Analysing the causes and measures of economic policy -- Effects of the increasing shadow economy -- The 'two-pillar strategy' -- Conclusion and outlook.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Informal sector (Economics); Business enterprises -- Corrupt practices; Commercial crimes; Tax evasion; Illegal aliens; Welfare fraud; Fraud